Development of a silicon diode detector for skin dosimetry in radiotherapy. Issue 10 (12th August 2017) - Vicoroski, Nikolina; Espinoza, Anthony; Duncan, Mitchell; Oborn, Bradley M.; Carolan, Martin; Metcalfe, Peter; Menichelli, David; Perevertaylo, Vladimir L.; Lerch, Michael L. F.; Rosenfeld, Anatoly B.; Petasecca, Marco
Abstract : Purpose: The aim of in vivo skin dosimetry was to measure the absorbed dose to the skin during radiotherapy, when treatment planning calculations cannot be relied on. It is of particularly importance in hypo‐fractionated stereotactic modalities, where excessive dose can lead to severe skin toxicity. Currently, commercial diodes for such applications are with water equivalent depths ranging from 0.5 to 0.8 mm. In this study, we investigate a new detector for skin dosimetry based on a silicon epitaxial diode, referred to as the skin diode. Method: The skin diode is manufactured on a thin epitaxial layer and packaged using the "drop‐in" technology. It was characterized in terms of percentage depth dose, dose linearity, and dose rate dependence, and benchmarked against the Attix ionization chamber. The response of the skin diode in the build‐up region of the percentage depth dose (PDD) curve of a 6 MV clinical photon beam was investigated. Geant4 radiation transport simulations were used to model the PDD in order to estimate the water equivalent measurement depth (WED) of the skin diode. Measured output factors using the skin diode were compared with the MO S kin detector and EBT3 film at 10 cm depth and at surface at isocenter of a water equivalent phantom. The intrinsic angular response of the skin diode was also quantified in charge particle equilibrium conditions (CPE) and at the surface of a solid water phantom. Finally, the radiation hardness of the skin diode up to an accumulated dose of 80 kGy using photons from a Co‐60 gamma source was evaluated. Results: The PDD curve measured with the skin diode was within 0.5% agreement of the equivalent Geant4 simulated curve. When placed at the phantom surface, the WED of the skin diode was estimated to be 0.075 ± 0.005 mm from Geant4 simulations and was confirmed using the response of a corrected Attix ionization chamber placed at water equivalent depth of 0.075 mm, with the measurement agreement to within 0.3%. The output factor measurements at 10 cm depth were within 2% of those measured with film and the MO S kin detector down to a field size of 2 × 2 cm 2 . The dose–response for all detector samples was linear and with a repeatability within 0.2%. The skin diode intrinsic angular response showed a maximum deviation of 8% at 90 degrees and from 0 to 60 degree is less than 5%. The radiation sensitivity reduced by 25% after an accumulated dose of 20 kGy but after was found to stabilize. At 60 kGy total accumulated dose the response was within 2% of that measured at 20 kGy total accumulated dose. Conclusions: This work characterizes an innovative detector for in vivo and real‐time skin dose measurements that is based on an epitaxial silicon diode combined with the Centre for Medical Radiation Physics (CMRP) "drop‐in" packaging technology. The skin diode proved to have a water equivalent depth of measurement of 0.075 ± 0.005 mm and the ability to measure doses accurately relative to reference detectors.